2018
DOI: 10.3892/or.2018.6776
|View full text |Cite
|
Sign up to set email alerts
|

Combination of serum microRNAs and ultrasound profile as predictive biomarkers of diagnosis and prognosis for papillary thyroid microcarcinoma

Abstract: Circulating microRNAs (miRNAs) are promising diagnostic markers in various types of cancers, including papillary thyroid carcinoma (PTC). However, there is sparse information reported with regards to miRNA expression in papillary thyroid microcarcinoma (PTMC) or concerning the role of a combination of miRNAs and ultrasound (US) in the diagnosis of PTMC before surgery. Therefore, we designed a study that aimed to evaluate miRNA expression levels and their potential associations with US findings and determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…To our best knowledge, miR-181b and miR-21 have not been investigated in plasma as possible biomarkers of PTC, although they have been found to be overexpressed in PTC tissue samples [14,18,25]. Furthermore, miR-21 was analyzed in serum samples and showed potential to become a diagnostic and prognostic marker of PTC [42,43]. We found a significant overexpression of plasma miR-222 in PTC compared to NG.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To our best knowledge, miR-181b and miR-21 have not been investigated in plasma as possible biomarkers of PTC, although they have been found to be overexpressed in PTC tissue samples [14,18,25]. Furthermore, miR-21 was analyzed in serum samples and showed potential to become a diagnostic and prognostic marker of PTC [42,43]. We found a significant overexpression of plasma miR-222 in PTC compared to NG.…”
Section: Discussionmentioning
confidence: 70%
“…We chose to analyze miRNA expression in plasma samples because this bioliquid is prevented from clotting [40,41]. Certain studies have already shown changes in circulating miRNA expression in PTC patients [42][43][44]. Our findings suggest that these five miRNAs are overexpressed in PTC and spread from PTC cells to the bloodstream at detectable levels.…”
Section: Discussionmentioning
confidence: 78%
“…Increasing attention has come to be attracted on the function of miRNAs as important biomarkers or mediators underlying the tumorigenesis of thyroid [24,25]. The current study mainly addressed the specific functions of miR-30d and molecular mechanisms by which miR-30d involved in the development of thyroid cancer, and our results presented that miR-30d could promote cell apoptosis through mediating USP22/SIRT1/FOXO3a/PUMA axis, thereby slowing down thyroid tumorigenesis ultimately (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Seven articles used benign thyroid nodule (BTN) patients as controls, and two articles 14,15 using both BTN patients and healthy people as controls. One article 16 studied papillary thyroid micro carcinoma (PTMC) patients, and other eight articles studied PTC patients. six articles were prospective studies, and three articles 5,15,17 were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%